Functional diversity of staphylococcal surface proteins at the host-microbe interface - Schwermann, Nicoletta; Winstel, Volker (Frontiers in Microbiology, 2023)
Surface proteins of Gram-positive pathogens are key determinants of virulence that substantially shape host-microbe interactions. Specifically, these proteins mediate host invasion and pathogen transmission, drive the acquisition of heme-iron from hemoproteins, and subvert innate and adaptive immune cell responses to push bacterial survival and pathogenesis in a hostile environment. Herein, we briefly review and highlight the multi-facetted roles of cell wall-anchored proteins of multidrug-resistant Staphylococcus aureus, a common etiological agent of purulent skin and soft tissue infections as well as severe systemic diseases in humans. In particular, we focus on the functional diversity of staphylococcal surface proteins and discuss their impact on the variety of clinical manifestations of S. aureus infections. We also describe mechanistic and underlying principles of staphylococcal surface protein-mediated immune evasion and coupled strategies S. aureus utilizes to paralyze patrolling neutrophils, macrophages, and other immune cells. Ultimately, we provide a systematic overview of novel therapeutic concepts and anti-infective strategies that aim at neutralizing S. aureus surface proteins or sortases, the molecular catalysts of protein anchoring in Gram-positive bacteria.